2007
DOI: 10.1002/jcla.20182
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ATP production in whole blood and lymphocyte proliferation in response to phytohemagglutinin

Abstract: Lymphocyte proliferation in response to mitogens, phytohemagglutinin (PHA), concanavalin A, pokeweed, and/or specific antigens has been the method of choice for in vitro diagnosis of cell-mediated immune dysfunction. Recently, an assay to measure intracellular adenosine triphosphate (ATP) production in response to PHA has been developed that requires a shorter, overnight incubation. We compared a standard 5- to 7-day lymphocyte mitogen stimulation assay utilizing tritiated thymidine (3H-thy) incorporation to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…With increasing number of transplantations being performed in the pediatric age group, an ideal method of monitoring immune status of post‐transplant pediatric patients is still lacking. The Cylex assay, which requires a very small of amount of whole blood and has a rapid turn around time, has been proposed as an early measure of immune status in few studies (4, 6–8). Studies have shown that the immune system evolves over childhood and has different characteristics compared to adults (9).…”
Section: Discussionmentioning
confidence: 99%
“…With increasing number of transplantations being performed in the pediatric age group, an ideal method of monitoring immune status of post‐transplant pediatric patients is still lacking. The Cylex assay, which requires a very small of amount of whole blood and has a rapid turn around time, has been proposed as an early measure of immune status in few studies (4, 6–8). Studies have shown that the immune system evolves over childhood and has different characteristics compared to adults (9).…”
Section: Discussionmentioning
confidence: 99%
“…One assay that we use is the ImmunKnow assay (www.cylex.net). This is an assay that detects changes in CD4 cell ATP production, a known biomarker of global immune function [5,6], and is FDA approved to detect function of T cells in immunosuppressed populations. One drawback of this assay is that the blood must be tested within 30 h of drawing from the patient and many centers do not offer Cylex testing and the blood must be shipped to the testing center.…”
Section: Key Pointsmentioning
confidence: 99%
“…The ATP assay can be used to evaluate the functional integrity of living cells, since all cells need ATP for cellular functions. The ATP assay is especially useful, since its application is not limited to cancer cell lines (Augustine et al, 2007), and has a 100-fold higher sensitivity than that of the 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay for counting the number of cells (Hunter et al, 1993;Petty et al, 1995). It has shown excellent linearity and a wide dynamic range (0-750,000 RLU) in RPMI-8226 cells (Sekhon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%